"Your policy, my rationale". How individual and structural drivers influence European forest owners' decisions. (December 2018) - Deuffic, Philippe; Sotirov, Metodi; Arts, Bas
Abstract: If forest policies aim to orientate forest owners' behaviours, some gaps still remain between policy makers' objectives and forest owners' final decision. In order to understand where these discrepancies come from, we propose a conceptual framework which analyse forest owners' decision-making through the combination of four individual logics of action (utilitarism, appropriateness, cognition, and practices) and five main structural factors (forest policies, market, environment, knowledge, and social norms). Instead of identifying a profusion of very accurate profiles often too specific to a regional or national context, we also aim at attempting a generalization of "forest owners meta-profiles". Finally we distinguish five ones: "optimizers or economy-oriented", "satisfiers or traditional knowledge oriented", "passive or outsider", "environmentally-oriented", and "multifunctional public forest managers" Following this classification, we analysed the influence of structural factors such as public policies, market, environmental issues, knowledge, and social norms on decision making. Beyond this typology, we also identify some major trends in forest owners' attitudes: firstly, we show that forest owners adopt more easily forest policies which support the management activities that they have planned. They also may reshape those who do not fit with their goals. Although forest owners are not particularly in favour of the coercive power of the state, they appreciate this political authority as it create a legitimate arbiter and mediator for formal and negotiated agreements. Secondly, if the logic of utilitarism and factors as wood market are still important drivers for action, the respect of social norms (such as protecting the environment or managing the forest for public goods) gives less-profit-oriented forest owners a new legitimacy for action that did not exist 20 years ago. Finally, we also raise questions about the emergence of new forest owners who may reconsider their roles, and redefine forestry norms in the future instead of just following the rules.